Supertubes [carbon nanotubes]. - Avouris, P.
This paper discusses the different characteristics of carbon nanotubes which make them ideal for a number of potential applications ranging from ultrathin, breathable, waterproof fabrics to bright, rugged flat-panel displays for televisions and computer monitors. Carbon nanotubes can be far stronger than steel, lighter than aluminum and more conductive than copper. The electrical properties of carbon nanotubes are so attractive that researchers are already eyeing them as replacements for silicon circuits and are being considered as a most promising technology that may someday pick up where conventional CMOS devices lead off. As the dimensions of silicon CMOS transistors continue to shrink well into the next decade, problems resulting from increasing power dissipation, leakage currents, and variations in device parameters will continue to rise. If all goes well, carbon nanotube electronics will be poised to take over before the problems encountered by the continual downscaling of silicon CMOS dimensions become insurmountable.
Keywords: Carbon nanotubes; Dissipated power density; Electrical properties; Electronic nanotechnology; Low-power integrated electronic; Optical properties; Optoelectronic circuits; Optoelectronics technology; Silicon CMOS circuits